Does the Zambian water sector regulation have pro-poor tools and outcomes?. (2016) - Marson, Marta; Dijk, Meine Pieter Van
Zambian regulatory system was set up at the end of the '90s within the reform of the national water sector, based on the commercialisation of water utilities, and market orientation is among its most apparent features. However, data show that, in 13 years, jointly with important efficiency gains Zambian utilities also improved their social performances. We investigate how these pro-poor outcomes were achieved by analysing the regulatory tools, and conclude with a positive evaluation of the regulation system. Nonetheless, we also point to the limitations of pro-poor regulation when there is a shortage of investment finance.